Leigh Syndrome: A Tale of Two Genomes - Bakare, Ajibola B.; Lesnefsky, Edward J.; Iyer, Shilpa (Frontiers in Physiology, 2021)
Leigh syndrome is a rare, complex and incurable early-onset (typically infant or early childhood) mitochondrial disorder with both phenotypic and genetic heterogeneity. The heterogeneous nature of this disorder, based in part on the complexity of mitochondrial genetics, and the significant interactions between the nuclear and mitochondrial genomes has made it particularly challenging to research and develop therapies. This review article discusses some of the advances that have been made in the field to date. While the prognosis is poor with no current substantial treatment options, multiple studies are underway to understand the etiology, pathogenesis, and pathophysiology of Leigh Syndrome. With advances in available research tools leading to a better understanding of the mitochondria in health and disease, there is hope for novel treatment options in the future.